Rotorcraft engine maintenance costs analysis based on flight profile and usage. - Chrysochoidis, Evangelos (Cranfield University, 2018)
Rotorcraft cover all sectors of human activity, supporting military, civil and government needs. Their design allows them to: i) deploy at different operating environments, ii) support power-demanding flight profiles, and iii) be agile and highly maneuverable. Compared to a civil aircraft turbofan engine, which typically operates at 35,000 feet for several hours, turboshaft engines found on rotorcraft usually experience high-frequency power changes. This results in a decrease of the useful life of critical components, due to low cycle fatigue (LCF) considerations. Methods developed so far, regarding the effects of engine degradation on engine performance and the estimation of the life of critical components, relate to aircraft turbofan engines, and therefore are not directly transferable to rotorcraft engines. Moreover, the current methods available to assess engine life cycle maintenance cost are also based on aircraft-related considerations and therefore are inapplicable to rotorcraft operations. Specifically, the current erroneous assessment premise is that the rotorcraft engine experiences two fatigue cycles per flight. This may be true for an aircraft due to its simple flight profile, but it does not apply to a rotorcraft due to the inherent diversity of the mission. After a thorough literature review, this work identified a gap in the existing knowledge regarding the life cycle cost assessment of rotorcraft, which may operate on a plethora of mission profiles within a given timeframe. In addition, the review did not reveal any evidence of a tool that could be deployed in these cases, particularly to assess the effect of different component designs on life. To address the aforementioned limitations, this doctoral work established a new methodology to estimate turbine fatigue cycles according to the peculiarities of every mission profile. The method also assesses engine life cycle maintenance costs considering a mixture of several different flight profiles within a certain timeframe (instead of a single flight profile). The new toolset created can provide useful information to an operator, regarding turbine life limit estimations and incurred maintenance costs, also considering factors such as: i) the fleet operating environment, ii) the flight profiles used, iii) fleet numbers and expected availability and, iv) pilot experience and flight attitude. The proposed methodology regarding the turbine life estimation integrates: i) an in-house helicopter flight mechanics code, ii) an in-house tool, which calculates engine performance, and iii) a tool to assess the turbine life developed from the author. It creates a set of life-limits for three different flight profiles and then uses a newly developed method, named Weight Usage Flight Profile Method (WU-FPM). This estimates an ‘equivalent’ life-limit in flight hours based on the fatigue cycles limit, which was estimated from the three different flight profiles, over the duration of a year. The life-limit data set is based on a Design Of Experiment (DOE) approach. The DOE estimates a representative turbine life for a reference flight profile, based on a design space which considers two operating (payload and climb rate) and one environmental parameter (ISA deviation). These are chosen within the rotrocraft Original Equipment Manufacturer (OEM) -defined capabilities. The parameters used for this life-limit are used to estimate the life limit for a Search and Rescue (SAR ) and Oil and Gas ( OAG) flight profile. Regarding the maintenance cost assessment the methodology uses two scenarios to estimate the life cycle costs: i) the Minimum Shop Visit (MINSV), and ii) the maximum Life Limited Part (LLP) usage. The previously estimated ‘equivalent’ engine life due to turbine failure and the OEM-specified Time between Overhaul (TBO) are used to assess maintenance intervals, which support these scenarios. The new method established was applied to selected test cases to demonstrate and assess its functionality. Results showed that regarding the operational and environmental parameters that affect Turbine Entry Temperature (TET), the payload and the ISA deviation are the most significant in hover and cruise, while the climb rate is the more influential parameter in the climb segment. Results also showed that the number of fatigue cycles per flight change according to the mission flight profile. For example, for a passenger flight, the turbine experiences 4 fatigue cycles, while it experiences 10 on a Search and Rescue (SAR) and 12 on an Oil and Gas (OAG) flight. Regarding maintenance cost prediction, the results show that the diversity of the missions influences the incurred cost significantly. For example, the costs incurred for a mission distribution of Passenger/OAG/SAR of 80/10/10% respectively, compared to a distribution of 50/40/10% can increase engine service life by 17.5%. The developed methodology, combined with a surrogate model, can be a useful tool for a rotorcraft operator to support informed financial planning decisions, based on a short or longer-term analysis.
Keywords: Turbine fatigue cycles; fleet operating environment; engine performance; weight usage flight profile method (WU-FPM); ISA deviation; payload